Comparative profiling of stemness markers expressed by human umbilical vein endothelial cells and human umbilical cord matrix-derived stem cells - Hayati A.-R.; Adzman-Sellymiah; Chua K.-H.; Aqilah R.-N.F.; Tan G.-C.; Fatimah S.-S.; Lim Y.-H.; Nur Syahrina Rahim; Nur Fariha Mohd Manzor (J. K. Welfare and Pharmascope Foundation, 2024)
Indexed by Scopus